The Construction of Cerai Manis (Prefered Divorce) on the Border of Indonesia and Malaysia Communities - Ma'u, Dahlia Haliah; Wagiyem, Wagiyem; Rahayu, Rita Mustika (al-'adalah, 2023)
One of the implications of unregistered marriages between Indonesian-Malaysian border communities is the occurrence of non-litigation divorces or divorces outside of court. This implication happens because there is no evidence in the form of a marriage book that is officially regulated in Indonesia. Divorce referred to by the local community is known as cerai manis (preferred divorce). This type of divorce is done based on the willingness and agreement of both parties without any conflicts or disputes. The purpose of this research is to find out the construction of cerai manis law which is part of the customary law of the local community. The method used in this research is field research with a sociological approach, while for data analysis, the author used descriptive qualitative analysis techniques. The results of this research indicate that the parties who agree to divorce, after going through the stages of adat and customary mediation, will obtain a certificate of customary separation which also regulates child custody, rights to share over joint assets and collective agreements.